Nilai-nilai pendidikan Islam pada tradisi Bubur Asyura di Pondok Modern Asy-Syifa Balikpapan - Rohmatun, Nur; Azizah, Lila; Supriyatno, Triyo (LPPM Universitas Ibn Khaldun, Bogor, 2024)
This research describes; first, inspiration for the implementation of the Ashura porridge tradition. Second, the values of Islamic education in the Ashura porridge tradition. Third, the strategy for internalizing the values of Islamic education in the Ashura porridge tradition. This research method is qualitative. Data collection methods are observation, interviews, and documentation. The results of the research are first, inspiration for the implementation of the Ashura porridge tradition begins based on belief in the story of the Prophet Noah and his people who collected leftover food after the flood and processed it into porridge. This tradition is carried out every year on 10 Muharram. Second, The values of traditional Islamic education include the values of faith, sharia, and morals. Third, the internalization strategy used is habituation, experiential learning, and example. It can be concluded that there are Islamic educational values in the Ashura porridge tradition and to internalize them requires supporting strategies so that these values are easily attached to the students. Abstrak Penelitian ini mendeskripsikan: Pertama, Inspirasi Implementasi tradisi bubur Asyura; Kedua, Nilai-nilai pendidikan Islam pada tradisi bubur Asyura; Ketiga, Strategi internalisasi nilai-nilai pendidikan Islam pada tradisi bubur Asyura. Metode penelitian ini adalah kualitatif. Metode pengumpulan data dengan observasi, wawancara dan dokumentasi. Hasil penelitian yakni; pertama, inspirasi implementasi tradisi bubur Asyura diawali atas dasar kepercayaan terhadap kisah Nabi Nuh dan kaumnya yang mengumpulkan sisa makanan setelah banjir dan diolah menjadi sebuah bubur. Tradisi ini dilaksanakan setiap tahun pada 10 Muharram. Kedua, nilai-nilai pendidikan Islam tradisi ini meliputi nilai akidah, syariah dan akhlak. Ketiga, strategi internalisasi yang digunakan adalah pembiasaan, experiental learning dan keteladanan. Dapat disimpulkan terdapat nilai-nilai pendidikan Islam pada tradisi bubur Asyura dan menginternalisasikannya dibutuhkan strategi penunjang agar nilai-nilai tersebut dengan mudah melekat pada diri santri.